2022
DOI: 10.1186/s43055-021-00688-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of virtual teaching of diagnostic and interventional imaging fundamentals to Egyptian medical students: an analytical cross-sectional study

Abstract: Background There is a worldwide deficit in teaching and training in the field of radiology for undergraduate medical students. This educational gap is prominent in many medical schools as most radiology curricula are a part of other specialty trainings, usually provided by non-radiologists. After COVID-19 pandemic, there was an increased trend in online education. However, questions have been raised about the efficacy and acceptance of online education. We developed a course on the principles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The questionnaire was developed through an intensive review of the literature, [ 10 , 17 , 21 ] and reviewed by the research committee comprised of senior radiologists and other medical professionals with relevant research expertise. After discussion and review, the authors finalized the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire was developed through an intensive review of the literature, [ 10 , 17 , 21 ] and reviewed by the research committee comprised of senior radiologists and other medical professionals with relevant research expertise. After discussion and review, the authors finalized the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…[7] Multiple studies have shown that medical students worldwide lack the fundamental knowledge required for imaging indications and interpretations. [8][9][10] In Pakistan, the majority of medical students have limited knowledge about radiology, especially in their preclinical years. [11] Furthermore, medical students in Pakistan are not well versed when it comes to dosage and hazards that come with the utilization of radiological imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Creatinine and other waste items are removed from the blood by healthy JMRHS 6 (10), 2809-2814 (2023) kidneys (Rasooly et al,2015). Your body excretes filtered waste through your urine (Negm et al,2022). A higher level of creatinine may build up in the blood if the kidneys are not working correctly.…”
Section: Introductionmentioning
confidence: 99%